2020
DOI: 10.1084/jem.20191226
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting both proline biosynthesis and lipogenesis synergistically suppresses tumor growth

Abstract: Cancer cells often proliferate under hypoxia and reprogram their metabolism. However, how to find targets to effectively block the hypoxia-associated metabolic pathways remains unclear. Here, we developed a tool to conveniently calculate electrons dissipated in metabolic transformations. Based on the law of conservation of electrons in chemical reactions, we further built up an electron balance model for central carbon metabolism, and it can accurately outline metabolic plasticity under hypoxia. Our model spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…showed that under hypoxic conditions, proline synthesis and reductive carboxylation, both of which require NADPH, act as alternative bins for electrons so that electron transfer can occur for cellular proliferation [36]. These studies fit well with our observations, where D492M cells indeed have lower oxygen consumption rate [11] and show higher activity of aforementioned pathways.…”
Section: Alterations In Reductive Carboxylation and Redox Metabolism supporting
confidence: 91%
“…showed that under hypoxic conditions, proline synthesis and reductive carboxylation, both of which require NADPH, act as alternative bins for electrons so that electron transfer can occur for cellular proliferation [36]. These studies fit well with our observations, where D492M cells indeed have lower oxygen consumption rate [11] and show higher activity of aforementioned pathways.…”
Section: Alterations In Reductive Carboxylation and Redox Metabolism supporting
confidence: 91%
“…Accordingly, PYCR1 KD reduces BC cells proliferation and invasiveness and increases the cytotoxicity of chemotherapeutic drugs, thus suggesting that PYCR1 may be a potential therapeutic target for BC (31). Complementary to these findings, Liu et al developed a tool to calculate electrons energy dissipation during metabolic transformations (29), and found that under hypoxic conditions in which the electron transfer chain (ETC) to oxygen is blocked, proliferating cells rewire their metabolism and use Proline biosynthesis and lipogenesis as alternative electron acceptors. Blocking simultaneously ALDH18A1 and lipogenesis inhibits breast tumor growth in vivo and in vitro (29).…”
Section: Proline Biosynthesis Genes Predict Poor Prognosis In Cancermentioning
confidence: 99%
“…This activity might be essential in tumors, such as gliomas, that experience hypoxia and therefore limited ETC activity. Conditions that compromise mitochondrial ETC force cells to increase flux through the glutamine-proline pathway, in order to dissipate electron buildup through NADH oxidation by P5CS and PYCR enzymes 122,123 . This property of PYCR1 to act as a "mitochondrial vent" has wider implications.…”
Section: Proline Biosynthesis and The Tca Cyclementioning
confidence: 99%
“…However, whether this is functionally meaningful is doubtful, as ectopic expression of both the short and long P5CS isoforms in different cell lines had no overt effect on their proliferation or survival 38 . The role of P5CS is likely to be context-specific, as, in breast cancer, CRISPR/Cas9-mediated knockout of P5CS had no impact on tumor growth, but it sensitized cancer cells to pharmacological inhibition of lipogenesis, indicating that inhibition of proline biosynthesis could synergize with therapies targeting lipid metabolism 122 . Recently, increased expression of OAT has been shown to correlate with NSCLC progression, and OAT activity supports proliferation and metastatic spread of NSCLC cells 126 .…”
Section: Other Proline Enzymesmentioning
confidence: 99%
See 1 more Smart Citation